Long-range aerosol transport and impacts on size-resolved aerosol composition in Metro Manila, Philippines - Braun, Rachel A (Archīum Ateneo, 2020)
This study analyzes long-range transport of aerosol and aerosol chemical characteristics based on instances of high- and low-aerosol-loading events determined via ground-based size-resolved aerosol measurements collected at the Manila Observatory in Metro Manila, Philippines, from July to October 2018. Multiple data sources, including models, remote sensing, and in situ measurements, are used to analyze the impacts of long-range aerosol transport on Metro Manila and the conditions at the local and synoptic scales facilitating this transport. Through the use of case studies, evidence of long-range transport of biomass burning aerosol and continental emissions is identified in Metro Manila. Long-range transport of biomass burning aerosol from the Maritime Continent, bolstered by southwesterly flow and permitted by low rainfall, was identified through model results and the presence of biomass burning tracers (e.g., K, Rb) in the ground-based measurements. The impacts of emissions transported from continental East Asia on the aerosol characteristics in Metro Manila are also identified; for one of the events analyzed, this transport was facilitated by the nearby passage of a typhoon. Changes in the aerosol size distributions, water-soluble chemical composition, and contributions of various organic aerosol species to the total water-soluble organic aerosol were examined for the different cases. The events impacted by biomass burning transport had the overall highest concentration of water-soluble organic acids, while the events impacted by long-range transport from continental East Asia showed high percent contributions from shorter-chain dicarboxylic acids (i.e., oxalate) that are often representative of photochemical and aqueous processing in the atmosphere. The low-aerosol-loading event was subject to a larger precipitation accumulation than the high-aerosol events, indicative of wet scavenging as an aerosol sink in the study region. This low-aerosol event was characterized by a larger relative contribution from supermicrometer aerosols and had a higher percent contribution from longer-chain dicarboxylic acids (i.e., maleate) to the water-soluble organic aerosol fraction, indicating the importance of both primary aerosol emissions and local emissions.